Vanishing Universal Norms? Rethinking Erga Omnes in International Humanitarian Law Principles - Manitra, Ramalina Ranaivo Mikea; Bourdeau, Callista Putri; Kylatifa Ghaniya Aristi; Muhammad Hazel Nailah Akbar (Brawijaya Law Journal, 2025)
International humanitarian law (IHL) is grounded on principles intended to apply universally in situations of armed conflict. Yet, the persistence of widespread violations in recent conflicts raises questions about the practical effectiveness of these legal norms. This paper investigates whether the erga omnes character of IHL principles still holds meaningful legal force or is increasingly relegated to symbolic rhetoric. Employing a doctrinal legal method, it explores the legal foundation and evolution of erga omnes, their intersection with IHL, and their invocation in contemporary conflict contexts. The analysis finds that while obligations erga omnes reflect a shared international commitment, their enforcement remains inconsistent and often influenced by political considerations. The study also observes that appeals to universality can serve as moral and legal pressure points—particularly important in influencing decision-makers who shape global responses to humanitarian crises. The paper concludes that without strengthened mechanisms for accountability, the obligations erga omnes in IHL principles risk being reduced to aspirational language rather than enforceable law.